2016
DOI: 10.1037/lat0000053
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-exposed Latina immigrants’ networks: A social network analysis approach.

Abstract: Objective Trauma exposure among Latina immigrants is common. Social support networks can buffer the impact of trauma on mental health. This study characterizes the social networks of trauma-exposed Latina immigrants using a social network analysis perspective. Methods In 2011–2012 a convenience sample (n=28) of Latina immigrants with trauma exposure and presumptive depression or posttraumatic stress disorder was recruited from a community clinic in Washington DC. Participants completed a social network asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…In this study, the vast majority of the four most important people named by participants were family members, and very few were nonfamily members. The importance of immediate and extended family members to people of Mexican origin that we observed in our study is consistent with previous research on Latinos documenting the centrality of family (Campos & Kim, 2017;Hurtado-de-Mendoza et al, 2016;Katiria Perez & Cruess, 2014;Sabogal et al, 1987). Perhaps support, whose primary source is family as in our study, may contribute to psychological well-being by facilitating social integration and providing opportunities for everyday social interactions and shared activities, and thereby attenuating negative experiences (Cohen, 2004;Lakey & Orehek, 2011).…”
Section: Main Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the vast majority of the four most important people named by participants were family members, and very few were nonfamily members. The importance of immediate and extended family members to people of Mexican origin that we observed in our study is consistent with previous research on Latinos documenting the centrality of family (Campos & Kim, 2017;Hurtado-de-Mendoza et al, 2016;Katiria Perez & Cruess, 2014;Sabogal et al, 1987). Perhaps support, whose primary source is family as in our study, may contribute to psychological well-being by facilitating social integration and providing opportunities for everyday social interactions and shared activities, and thereby attenuating negative experiences (Cohen, 2004;Lakey & Orehek, 2011).…”
Section: Main Effectssupporting
confidence: 93%
“…Based on past research in the general population and Latino populations, we expected to find support for all four conceptual models among people of Mexican origin, and that the composition and nature of their social relationships would reflect cultural practices, values, and beliefs. People of Mexican origin tend to have larger and more intimate networks than other groups (Keefe, 1984; Mindel, 1980), and family plays an important and central source of social support for Latinos more broadly (Hurtado-de-Mendoza et al, 2016; Katiria Perez & Cruess, 2014; Sabogal, Marin, Otero-Sabogal, Vanoss, & Perez-Stable, 1987). Additionally, given the cultural ideal of establishing and maintaining close and harmonious relationships among Latinos (Campos & Kim, 2017), social support may play a more prominent role than social undermining in their psychological well-being.…”
Section: Study Purposementioning
confidence: 99%
“…Our study demonstrated that ethnic pride plays a buffering role above and beyond the influence of acculturation. Also given the cultural emphasis on familismo —a core cultural value characterized as cohesion, obligation, and reciprocity toward one’s family members (Hurtado-de-Mendoza et al, 2016)—in the Latinx community, impairment in interpersonal functioning may be a unique, yet salient path that links childhood trauma exposure and depressive mood among Latina mothers.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have begun to explore factors that influence negative psychological outcomes of early adversity and trauma, frequently highlighting the key role of interpersonal relationships. For Latina immigrant families, the crucial role of children (i.e., cultural broker) as a unique source of social support for parents has been frequently highlighted (Hurtado-de-Mendoza et al, 2016) and for ethnically diverse single mothers, social strains (the absence of social support) was found to mediate the relationship between cumulative trauma and PTSD symptoms (Samuels-Dennis, Ford-Gilboe, Wilk, Avison, & Ray, 2010).…”
Section: Childhood Trauma Depression and Interpersonal Functioningmentioning
confidence: 99%